Pengembangan Sistem Informasi Perpustakaan Untuk Meningkatkan Kinerja Layanan Perpustakaan - Milka Ranggatau (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2019)
Library Information System that is used by the library of Atma Jaya Makassar University (UAJM) is currently used to assist library management in cataloging, book circulation, procurement and membership but there are problems in service to students who cannot be handled. Lack of services to students such as information on book content, services for access to theses, thesis examination services, library free services, book request services, and a slow service process. In this study, the author develops the UAJM library information system that is used today by synchronizing student data in the added services and the current system used with SIAMIK. Development is carried out by adding information services needed by students such as the problems that the author describes. System testing results are considered feasible as the development of the previous system and the resulting system can be used by students in obtaining the information needed so that the performance of services to students increases.